Hasil Cross Product dari Dua Graf-k - Rizza Lestari; Rizky Rosjanuardi; Sumanang Muhtar Gozali (Jurnal EurekaMatika, 2022)
This article discusses results of cross product of two k-graphs. This study discusses the structure of the k-graphs, which consists of category and functor that satisfying the factorisation property. Furthermore, we discussed the crossed product results from two k-graphs, which includes product category and functor for such product category. Then an illustration is given on how to form a (k_1+k_2)-graph from two different k-graphs, namely k_1-graph and k_2-graph.Keywords: Category, Cross Product, Functor, Functor for Product, k-Graph.AbstrakArtikel ini membahas tentang hasil cross product dari dua graf-k. Dalam penelitian ini dibahas mengenai struktur dari graf-k, yang terdiri dari kategori dan fungtor yang memenuhi sifat faktorisasi. Selanjutnya dibahas bagaimana hasil cross product dari dua graf- k, yang mencakup produk kategori dan fungtor untuk produk kategori tersebut. Lalu diberikan ilustrasi bagaimana membentuk graf-(k_1+k_2)dari dua graf-k yang berbeda, yaitu graf-k_1 dan graf-k_2.